TRANSFORMASI PRIBADI MELALUI PENGALAMAN ANTARBUDAYA: STUDI KUALITATIF MAHASISWA IISMA DI LUAR NEGERI - Jolin (Puslitabmas Batam Tourism Polytecnic, 2025)
The Indonesian International Student Mobility Awards (IISMA) is an impactful program designed to give Indonesian students global exposure through academic and cultural exchange. This qualitative research explores the experiences of IISMA participants at Phoenix Academy, Western Australia. This research uses reflective journals, interviews, and documentation of program activities to identify the key themes: academic development, cultural adaptation, global networking, and the role of students as cultural ambassadors. Participants reported significant improvements in academic competencies, such as critical thinking and public speaking, developed through innovative, flipped learning methods. They successfully overcome cultural and linguistic barriers, increasing resilience and cross-cultural communication skills. By organizing and participating in cultural events, they effectively showcased Indonesian heritage on the international stage, while strengthening their national identity. Furthermore, activities such as the Capstone Project, industry visits to PwC, and excursions to iconic Western Australian destinations offered a deep understanding of global dynamics and collaborative teamwork. These experiences prepare participants for international collaboration while fostering a strong sense of pride in their Indonesian heritage.